Analisis Profit Margin dan Return on Aset Untuk Menilai Kinerja Keuangan Pada PT Asuransi Multi Artha Guna Tbk - Agus Sunaryo; Muhamad Ohorella (Sekolah Tinggi Ilmu Ekonomi Port Numbay Jayapura, 2020)
Analysis of Profit Margin and Return on Assets to Assess Financial Performance at PT Asuransi Multi Artha Guna Tbk. The results of the study show that 1) In general, the financial performance of PT Asuransi Multi Artha Guna Tbk (Persero) Tbk based on the ratio of Profit margin and Return On Assets can generate profits but the results of the ratio of Profit margin and Return On Assets can be said to be inefficient, because the results of Profit margin ratio figures have decreased while Return On Assets have increased 2) The development of Profitability Ratios of PT Asuransi Multi Artha Guna Tbk (Persero) Tbk has not been efficient even though it is able to generate profits every year this is because the development in each Profit margin ratio has decreased while Return On Assets has increased but not significantly decreased from the results of the ratio development in each year can occur because assets are not managed efficiently and also there is an increase in costs each year, causing low net income and the company's financial performance is not so good.Keywords: Profit Margin, Return On Assets and Financial Performance.